Islam dan Pergeseran Budaya di Tanah Bugis - Dwiyama, Fajri (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2024)
This article examines the impact of Islamic civilization on cultural shifts in the land of Bugis, South Sulawesi, Indonesia. Through historical and anthropological analysis, this research reveals how the entry of Islam in the 17th century significantly changed the cultural, social, and political landscape of the Bugis people. This study examines the transformation in the belief system, social structure, customary practices, and collective identity of the Bugis people as a result of interaction with Islamic civilization. The findings show that despite substantial changes, the Bugis people have managed to retain key elements of their cultural heritage, creating a unique synthesis between local traditions and Islamic values.